Substrate Protein Interactions and Methylglyoxal Modifications Reduce the Aggregation Propensity of Human Alpha-A-Crystallin G98R Mutant - Santhoshkumar, Puttur; Sharma, Krishna K. (Frontiers in Molecular Biosciences, 2022)
The G98R mutation in αA-crystallin is associated with presenile cataract development in humans. Previous studies have indicated that mutant proteins altered structure, decreased stability, increased oligomeric size, loss of chaperone-like activity, and susceptibility to proteolysis could be contributing factors to cataract formation. To evaluate the effect of substrate protein interactions with the mutant protein on cataract formation, we have performed chaperone assays with alcohol dehydrogenase (ADH), citrate synthase (CS), and βB2-crystallin (βB2), and analyzed the reaction mixtures by multi-angle light scattering (MALS) analysis. It appears that αAG98R protein initially gets stabilized upon interaction with substrate proteins. Analysis of the chaperone-client protein complexes revealed that wild-type αA-crystallin interacts with substrate proteins to form compact complexes leading to a slight increase in oligomeric mass, whereas αAG98R forms less compact and high molecular weight complexes with the substrate, and the resulting complexes continue to increase in size over time. As a result, the soluble complexes formed initially by the mutant protein begin to scatter light and precipitate. We found that the stability and chaperone activity of the αAG98R can be improved by modifying the protein with low concentrations (50 µM) of methylglyoxal (MGO). Incubation of αAG98R protein (1 mg/ml) under aseptic conditions for thirty days at 37°C resulted in precipitation of the mutant protein. In contrast, mutant protein incubations carried out with 50 µM MGO remained soluble and transparent. SDS-PAGE analysis showed gradual autolysis of the mutant protein in the absence of MGO. The average molar mass of the mutant protein oligomers changed from 7258 + 12 kDa to 3950 + 08 kDa within 60 min of incubation with MGO. There was no further significant change in the molar mass of mutant protein when tested on day 7 of MGO treatment. Our data suggest that the initial stabilization of αAG98R by substrate proteins could delay congenital cataracts' appearance, and the uncontrolled long-term interaction amongst mutant subunits and substrate proteins could be the rationale behind presenile cataracts formation. The results also demonstrate the potential benefit of low concentrations of MGO in stabilizing mutant chaperone protein(s).